2016
DOI: 10.1007/s00535-016-1213-1
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences among eosinophilic esophagitis, proton-pump inhibitor-responsive esophageal eosinophilia, and reflux esophagitis: comparisons of clinical, endoscopic, and histopathological findings in Japanese patients

Abstract: Comparisons of clinical, endoscopic, and histopathological findings between EoE and PPI-REE showed that these two types have similar characteristics, though EoE patients showed a higher atopic background. Predicting PPI responsiveness in cases with esophageal eosinophilia is difficult and requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
5
24
1
2
Order By: Relevance
“…We retrospectively enrolled patients with EE, including EoE ( n = 17) and PPI‐REE ( n = 33), as EoE was still rare in Asian populations. Consistent with studies conducted in Western countries, we have recently reported that the clinical characteristics including endoscopic findings did not differ between EoE and PPI‐REE . In this study, the specific endoscopic findings were mainly assessed by viewing endoscopic still photographs, with some cases confirmed by video.…”
Section: Discussionsupporting
confidence: 69%
“…We retrospectively enrolled patients with EE, including EoE ( n = 17) and PPI‐REE ( n = 33), as EoE was still rare in Asian populations. Consistent with studies conducted in Western countries, we have recently reported that the clinical characteristics including endoscopic findings did not differ between EoE and PPI‐REE . In this study, the specific endoscopic findings were mainly assessed by viewing endoscopic still photographs, with some cases confirmed by video.…”
Section: Discussionsupporting
confidence: 69%
“…Subepithelial inflammation may also trigger the destruction of the basal cell layer and lead to upward papillae elongation, but not a downward papillae elongation. Heterogeneity in endoscopic and histological findings has previously been reported in cases of EoE[31]. In fact, cases with “non-EoE-like endoscopic and histological findings” are more likely to represent sEoE than EoE.…”
Section: Discussionmentioning
confidence: 94%
“…No significant difference has been shown regarding the treatment efficacy between children and adults, between the dose and number of PPI administered, or between the absence and the presence of GERD [122]. Although evidence of the pathogenesis of PPI-REE and EoE is accumulating, the two entities cannot be clearly differentiated solely based on patient characteristics, symptoms, endoscopic findings, histological findings with immunostaining, or molecular findings [116,123,124]. Thus, some experts have proposed that the responsiveness to PPI should not be included in the diagnostic criteria for EoE, and that use of the term PPI-REE should be avoided [116].…”
Section: Drug: Ppi Therapymentioning
confidence: 99%